Impact of an On-Site Versus Remote Patient Navigator on Pediatricians' Referrals and Families' Receipt of Resources for Unmet Social Needs - Emily Messmer; Annelise Brochier; Marie Joseph; Yorghos Tripodis; Arvin Garg (SAGE Publishing, 2020)
Background: Patient navigation is increasingly being used by pediatric health care delivery systems to address patients' unmet social needs. However, it is not known whether navigators working remotely can be as effective at linking families to community resources as on-site navigators. The aim of this study was to assess whether a patient navigator located on-site versus remotely is more likely to receive referrals from clinicians, successfully follow-up with patients, and assist families with enrollment in social needs resources. Methods: A patient navigator worked on-site and remotely as she divided her time between 4 federally qualified health centers (FQHCs) from May 2015 to June 2019. We conducted a 1-sample test of proportion comparing the proportion of on-site referrals made with the proportion of the week spent in each FQHC. To assess the impact of on-site versus remote referrals on number of contacts with a family, we conducted a 2-sample t test. We used chi-square testing to assess the effect of on-site versus remote status on resource enrollment. Results: Of the referrals (N = 414) made to the patient navigator, the majority were made through the electronic health record (83%) versus in person (17%) ( P < .0001). When the navigator was on-site, significantly more referrals were made than expected (45% vs 29%, P < .0001). Between remote and on-site referral groups, there was no significant difference in number of contact points (1.0 vs 1.1 points, P = .32) or in the proportion of families who received a resource (4.6% vs 5.1%, P = .31). Conclusion: Our results indicate that clinicians were significantly more likely to refer families to patient navigation if the navigator was on-site. The likelihood of having contact with the navigator and enrolling in a resource, however, did not differ between families referred when the patient navigator was on-site compared with remote.